Coupled flow-geomechanics studies on the role of hydrofracturing and secondary fracturing in CO2-enhanced coalbed methane. Issue 5 (September 2021) - Guo, Chaobin; Feng, Quanlin; Ma, Tianran; Wang, Siqi; Zhou, Rui; Wang, Bo
CO2 -enhanced coalbed methane (CO2 -ECBM) can improve coalbed methane production efficiency and simultaneously alleviate greenhouse gas emissions. In this paper, we integrated TOUGH2 and FLAC3D numerical simulation software to conduct hydro-mechanical coupling analysis for effects of hydrofracturing and secondary fracturing in CO2 -ECBM. The simulation results show that the hydrofracturing and secondary fracturing treatments significantly increase the coal seam interconnectivity, enhancing overall injection and production. The reduction of the pore pressure near injection wells can effectively reduce the damage of gas injection well. Moreover, secondary fracturing can even increase cumulative gas production up to 32.5%. In addition to rising fracture density, increasing the fracture length is also considered an efficacious procedure for enhancing permeability in the secondary fracturing process.